Fast-Track Cardiac Anaesthesia at a Tertiary Care Cardiac Centre in Nepal - Pokharel, Jeju Nath; Sharma, Apurba; Upreti, Murari Raj; Koirala, Raamesh; Sharma, Jyotindra; Pradhan, Siddartha (Nepalese Heart Journal, 2014)
Background: With the evolution of anesthesia and surgical procedures, fast track cardiac anaesthesia has gained an increased interest, mainly based on the possibility of reducing health costs without compromising patient care and has been implemented at a tertiary care cardiac centre in Nepal. Objective: The purpose of this study is to evaluate the status of fast track cardiac anaesthesia after open heart procedures and suitability of existing anaesthetic technique for fast-track extubation. Methods: After standard anaesthesia and surgical technique, we retrospectively reviewed the duration of mechanical ventilation, length of Intensive Care Unit stay, reintubation, and incidence of inhospital mortality in consecutive adult patients undergoing open heart surgery during six months period. Results: The median time of the extubation was six hours, median days of the ICU stay was three days. Five cases were reintubated because of the respiratory failure which is about 1.8% out of 277 cases. Seven patients (2.5%) died of sepsis and low cardiac output syndrome. Conclusions: Fast track anaesthesia is suitable with applied anesthetic technique in our centre. However there exists relatively small risk of re-intubation (1.8%). Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 6-11 DOI: http://dx.doi.org/10.3126/njh.v10i1.9739